2018
DOI: 10.1021/acs.orglett.7b03996
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating Emission of [2]Rotaxane Driven by Chemical Fuel

Abstract: A molecular shuttle consisting of a dibenzo-24-crown-8 macrocycle and an axle with two degenerate peripheral triazolium stations, a central dibenzyl ammonium station, and two anthracenes stoppers was exposed to 2-cyano-2-phenylpropanoic acid as a chemical fuel. Protonation/deprotonation of the amine reversibly switches the rotaxane from a static and little emissive to a dynamic fluorescent shuttling device, the latter exhibiting rapid motion (15 kHz at 25 °C). Four fuel cycles were run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 46 publications
(24 reference statements)
0
31
1
1
Order By: Relevance
“…Interestingly, proton exchange from 2 to 2 H + and vice versa results to be fast on NMR timescale. This finding contrasts with that obtained in the case of two previously reported molecular machines driven by fuel 1 ,H, one based on a catenane [5a] and the other on a rotaxane [5e] structure. Moreover, in the present case, the absence of any signal ascribable to the ion pair 2 H + ⋅ArC(CH 3 )CN − (state B” ) during the whole 1 H NMR monitoring of the reaction, is in accordance with a very fast back proton transfer from 2 H + to ArC(CH 3 )CN − .…”
Section: Resultscontrasting
confidence: 99%
“…Interestingly, proton exchange from 2 to 2 H + and vice versa results to be fast on NMR timescale. This finding contrasts with that obtained in the case of two previously reported molecular machines driven by fuel 1 ,H, one based on a catenane [5a] and the other on a rotaxane [5e] structure. Moreover, in the present case, the absence of any signal ascribable to the ion pair 2 H + ⋅ArC(CH 3 )CN − (state B” ) during the whole 1 H NMR monitoring of the reaction, is in accordance with a very fast back proton transfer from 2 H + to ArC(CH 3 )CN − .…”
Section: Resultscontrasting
confidence: 99%
“…In the following, the addition of TFA initiated a second self-sorting. It was shown that the acid protonated the ligand 49, expelling zinc(II) from the complex [Zn 49 [62,63] as a chemical fuel, the protonation of 49 entailed the same cascade translocation resulting in SelfSORT-II but now with the effect that it slowly reversed back to the initial state (Figure 15b). Here, all translocations happen in an off-equilibrium system.…”
Section: Double Self-sorting (Only Structural)mentioning
confidence: 99%
“…We next investigated the operation of 1 under transient protonation conditions. Amongst the recently reported chemical fuels for artificial dissipative systems, the base‐catalyzed decarboxylation of carboxylic acids such as 2‐cyano‐2‐arylpropanoic acids and trichloroacetic acid (CCl 3 CO 2 H) has the ability to temporarily switch the global pH of the reaction medium from basic to acidic for definable periods of time. Trichloroacetic acid has the additional advantage that the only waste products of the fuel are carbon dioxide and chloroform, a volatile solvent.…”
Section: Figurementioning
confidence: 99%